"Assignment to Berlin" – realia pracy korespondentów amerykańskich w Niemczech w latach 1939–1941 - Sołuba, Paulina (Acta Universitatis Lodziensis. Folia Historica, 2015)
Berlin during the time of war was an interesting place for American correspondents. They could learn on the spot about further military plans, which the Nazi had. Equally important for them were to understand the mood of the Germans and their attitude toward war. Their observations was contradictory in relation to the press reports published in both German and Allied Press. Due to the existence of unofficial censorship in the Reich correspondents could not fairly and accurately inform readers about the progress of hostilities, the issue of rationing, bombing or negative feelings toward regime in German society. In a similar situation they were also journalists stationed in London or other European capitals. In this aspect, Berlin was part of a general trend. During the war, due to the decrease in the number of foreign journalists, American correspondents began play leading role in the journalistic circle in Germany. They were citizens of a neutral state, but so powerful that the Nazis wanted to keep him out of the armed conflict. For this reason, the Americans were treated very well. Despite this fact, the Americans very often wanted to leave the Berlin post. This was, in large part, because of their anti-Nazi feelings and depression caused by the successes of the German army.